Alterations of limbic structure volumes and limbic covariance network in patients with cluster headache. (September 2022) - Lee, Dong Ah; Lee, Joonwon; Lee, Ho-Joon; Park, Kang Min
Highlights: We found differences in the volumes of the limbic structures in cluster headache. Cluster headache showed significant alterations of the limbic covariance network. Alteration of limbic structures could be related to the cluster headache pathology. Abstract: The aim of this study was to compare the limbic structures and covariance network in patients with cluster headache to those of healthy controls. We enrolled 23 patients with newly diagnosed cluster headache and 31 healthy controls. They underwent three-dimensional T1-weighted imaging utilizing a 3.0 Tesla MRI scanner. Volumetric analysis of the subcortical limbic structures, including the hippocampus, amygdala, thalamus, mammillary body, hypothalamus, basal forebrain, septal nuclei, fornix, and nucleus accumbens, was performed. We examined the limbic covariance network using a graph theory. The volumes of the limbic structures between patients with cluster headache and healthy controls were significantly different. The volume of the left hippocampus in patients with cluster headache was significantly lower than that in healthy controls (0.256 vs 0.291 %, p  = 0.002). Patients with cluster headache showed significant alterations of the limbic covariance network. The average strength, global efficiency, local efficiency, mean clustering coefficient, and transitivity were lower (5.238 vs 10.322, p  = 0.030; 0.355 vs 0.608, p  = 0.020; 0.547 vs 1.553, p  = 0.020; 0.424 vs 0.895, p  = 0.016; respectively), whereas the characteristic path length was higher (3.314 vs 1.752, p  = 0.040) in patients with cluster headache than in healthy controls. We detected alterations of limbic structure volumes in patients with cluster headache compared to healthy controls, especially in the hippocampus. We also found significant alterations in the limbic covariance network in patients with cluster headache who showed decreased segregation and integration. These abnormalities could be related to the pathophysiology of cluster headache.